Blurred lines: intimacy, mobility, and the social military. Issue 1 (3rd May 2016) - Adey, Peter; Denney, David; Jensen, Rikke; Pinkerton, Alasdair
ABSTRACT: This paper, whilst drawing on a wide-scale exploration of social media use within the UK Armed Forces, narrates the visit of two academic researchers to a very particular military space: a Royal Navy warship. It does so in order to experience, question, and understand the extent to which social media cuts through the private, domestic or public, personal and familial, work and home in an intimate clinch of relations. We do so by exploring how the now-familiar story of the befuddlement of distance in contemporary conflict is complicated by remote communications and autonomous technologies. And we do so to explore the ways in which social media might reconfigure quite intimate and gender ed social relations and practices. This narrative, we suggest, needs nuancing through the military lives, however far removed, who live closeness and distance in differentiated ways, particularly through their mobile phones, tablets, and computers. We explore, through a number of focus groups with naval personnel on board a military ship, how the reworking of military life is producing feelings of distance and isolation, but also togetherness and community. Indeed, as opposed to simply opening up once-intimate places to exposure and, thus, erasing geography, instead, places and spaces, and bodies, matter differently. Crucial to uncovering and understanding these relations are our own embodiments as researchers. We explore how we as academic researchers erode and rework these distinctions as we navigate, and inhabit, particular military spaces.